The International Functional Electrical Stimulation Society (IFESS): highlights from the IFESS conference at Rehabweek 2023 - Hamzaid, Nur Azah; Manaf, Haidzir; Azmi, Nur Liyana; Milosevic, Matija; Spaic, Erika G.; Yoshida, Ken; Gorgey, Ashraf S.; Ferrante, Simona (2024)
The annual conference of the International Functional Electrical Stimulation Society (IFESS) was held in conjunction with the 7th RehabWeek Congress, from September 24 to 28, 2023 at the Resorts World Convention Centre on Sentosa Island, in Singapore. The Congress was a joint meeting of the International Consortium on Rehabilitation Technology (ICRT) together with 10 other societies in the field of assistive technology and rehabilitation engineering. The conference features comprehensive blend of technical and clinical context of FES, a sustained value the society has offered over many years. The cross‐ and inter‐ disciplinary approach of medicine, engineering, and science practiced in the FES community had enabled vibrant interaction, creation, and development of impactful and novel contributions to the field of FES, translating FES directly into highly relevant and sustainable solutions for the users.